The role of adaptive strategies in plant naturalization - Wen‐Yong Guo; Mark van Kleunen; Marten Winter; Patrick Weigelt; Anke Stein; Simon Pierce; Jan Pergl; Dietmar Moser; Noëlie Maurel; Bernd Lenzner; Holger Kreft; Franz Essl; et al. (Ecology Letters, 2018)
Determining the factors associated with the naturalization of alien species is a central theme in ecology. Here, we tested the usefulness of a metric for quantifying Grime's seminal concept of adaptive strategies – competitors, stress‐tolerators and ruderals ( CSR ) – to explain plant naturalizations worldwide. Using a global dataset of 3004 vascular plant species, and accounting for phylogenetic relatedness and species’ native biomes, we assessed the associations between calculated C‐, S‐ and R‐scores and naturalization success for species exhibiting different life forms. Across different plant life forms, C‐scores were positively and S‐scores negatively associated with both the probability of naturalization and the number of regions where the species has naturalized. R‐scores had positive effects on the probability of naturalization. These effects of the scores were, however, weak to absent for tree species. Our findings demonstrate the utility of CSR ‐score calculation to broadly represent, and potentially explain, the naturalization success of plant species.